ANALISIS STRATEGI BISNIS KONVEKSI BAPAK IWAN - Aviani, Dhevi; Dewi, Sania Sintia; Fauziah, Syifa Putri; Yusuf, Ramayani (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2023)
Abstract This research aims to explore the processes and challenges faced by Mr. Iwan in running his home-based garment workshop. Employing a qualitative approach, we analyze Mr. Iwan's experiences in managing production, order fulfillment, and customer interactions. Findings highlight Mr. Iwan's strategies in overcoming daily constraints, along with the positive and negative impacts of operating a home-based garment workshop. The study provides insights into the dynamics of small-scale garment production and the contribution of home-based workshops to the local economy.Keywords: Home-based workshop, Qualitative analysis, Production management, Daily constraints, Positive impacts, Local economy